Strength, deformation, and equation of state of tungsten carbide to 66 GPa. (November 2021) - Brugman, B.L.; Lin, F.; Lv, M.; Kenney-Benson, C.; Popov, D.; Miyagi, L.; Dorfman, S.M.
Abstract: Strength, texture, and equation of state of hexagonal tungsten monocarbide (WC) have been determined under quasi-hydrostatic and non-hydrostatic compression to 66 GPa using angle-dispersive X-ray diffraction in the diamond anvil cell. Quasi-hydrostatic compression in a Ne pressure medium demonstrates that nanocrystalline WC is slightly less incompressible than bulk-scale WC, with respective bulk moduli of K0 = 377 ± 7 and 397 ± 7 GPa and pressure derivatives K0 ' = 3.8 ± 0.3 and 3.7 ± 0.3. This decrease in incompressibility with grain size is similar to behavior observed in other ceramics. Under nonhydrostatic compression, WC supports a mean differential stress of ∼12-15 GPa at plastic yielding, which occurs at ∼30 GPa. Strength in WC is anisotropic, with the (001) plane supporting 29-42% higher stress than stresses calculated from mean strain. Simulations using an Elasto-ViscoPlastic Self-Consistent model indicate that strength inferred from lattice strain theory may be overestimated due to effects of plastic deformation. Plastic deformation generates a texture maximum near 〈 2 ¯ 110 〉 in the compression orientation, initially through prismatic slip on the 10 1 ¯ 0 〈 1 ¯ 2 1 ¯ 0 〉 and 10 1 ¯ 0 〈 0001 〉 slip systems, followed by activation of pyramidal slip on 10 1 ¯ 1 〈 2 ¯ 113 〉 at ∼40-50 GPa. Graphical abstract: Image, graphical abstract